Financial Statement and Projection Preparation in Start-Up Ventures - Cassar, Gavin (The Accounting Review, 2009)
ABSTRACT: Using a representative sample of entrepreneurs who are in the process of starting a business, this study investigates the determinants of the preparation of financial statements and projections in start-up ventures. Consistent with predictions from information economics and contracting, I find that the use of outside funding, level of competition, and venture scale are positively associated with the intended frequency of financial statement preparation. However, comparing the economic significance of alternative influences suggests that the benefit of reducing competitive and fundamental uncertainty is more influential in explaining variations in intentions to prepare financial statements. Further, I find the determinants of preparation frequency vary among different financial statements; for instance, cash statements are more important for start-ups with products in earlier stages of development and with greater competition. In contrast to financial statements, the preparation of projections such as formal financial projections and regular sales forecasts by start-ups is positively associated with the importance of intangible investments such as patents, research and development, and with start-ups in high-tech industries.